Critical punishment memorialization in canada - Fiander, Sarah (Critical criminology, 2016)
Recent criminological scholarship on penal history museums has shown how sites of popular culture tend to silence the voices of prisoners and present them in ways that legitimate the deprivation of their liberty. While representations that reinforce the penal status quo are observable at most Canadian penal history sites, there are outliers that situate imprisonment as a form of oppression, and account for prisoners’ struggles and resistance. Drawing on three case studies from a 5-year qualitative research project on Canadian lock-up, jail, prison and penitentiary museums, we discuss what critical punishment memorialization looks like in a context of penal intensification in Canada. We show how such critical representations depend on the historical contextualization of penality as a manifestation of colonialism and/or the incorporation of prisoners’ voices and standpoint. We argue that the critical representations and narratives at these museum sites open up possibilities for the social distance between penal spectators and the incarcerated to be diminished by bringing humanizing prisoner narratives into focus in an otherwise dark tourist space.